Answer:
v1 = −2.201946 m/s ( to the left)
v2 = 0.7780534 m/s ( to the right)
Step-by-step explanation:
Given the following :
Mass of first glider (m1) = 0.149kg
Initial Speed of first glider (u1) = 0.710 m/s
Mass of second glider (m2) = 0.308kg
Initial Speed of second glider (u2) = 2.27m/s
For elastic collision:
m1u1 + mu2u2 = m1v1 + m2v2
Where V1 and v2 = final velocities if the body after collision.
Taking right as positive ; left as negative
u1 = 0.710m/s ; u2 = - 2.27m/s
u1 - u2 = - (v1 - v2)
0.710 - - 2.27 = - v1 + v2
v2 - v1 = 2.98 - - - - (1)
From:
m1u1 + mu2u2 = m1v1 + m2v2
(0.149 * 0.710) + ( 0.308 * - 2.27) = (0.149 * v1) + (0.308 * v2)
0.10579 + (-0.69916) = 0.149 v1 + 0.308v2
−0.59337 = 0.149 v1 + 0.308v2
Dividing both sides by 0.149
v1 + 2.067v2 = −0.59337 - - - - - (2)
From (1)
v2 = 2.98 + v1
v1 + 2.067(2.98 + v1) = −0.59337
v1 + 6.16 + 2.067v1 = −0.59337
3.067v1 = −0.59337 - 6.16
3.067v1 = −6.75337
v1 = −6.75337 / 3.067
v1 = −2.201946 m/s ( to the left)
From v2 = 2.98 + v1
v2 = 2.98 + (-2.201946)
v2 = 0.7780534 m/s ( to the right)